Child prostitution in Shamva in Zimbabwe. - Chirozva, Ireen (Midlands State University, 2017)
This research looks at the trends of Child Prostitution globally, in Africa, in Zimbabwe and in Shamva. It also focuses on the causes of child prostitution as the rate of child prostitution is increasing in Shamva day by day due to poverty, unemployment and violence and abuse. The effects of Child Prostitution and the intervention strategies used by the government as well as the Non-Governmental Organizations to curb child prostitution. Through the use of the information obtained from oral interviews with different people in Shamva including minor prostitutes, newspapers, reports, books as well as internet sources the research shows how deadly child prostitution is in Shamva.